Isolated Sulfite Oxidase Deficiency: MR Imaging Features - Dublin, Arthur B.; Hald, John K.; Wootton-Gorges, Sandra L. (American Journal of Neuroradiology, 2002)
Summary: Isolated sulfite oxidase deficiency is a rare autosomal inherited disorder of the normal degradation of sulfur-containing amino acids. Premature death in infancy secondary to severe neurologic deterioration is the usual outcome. This article provides an analysis, in temporal form, of brain imaging findings in this disorder.